Developmental Assets Predictors of Life Satisfaction in Adolescents - Soares, Ana Sofia; Pais-Ribeiro, José L.; Silva, Isabel (Frontiers in Psychology, 2019)
The concept of Developmental Assets links positive features of developmental ecologies with personal skills, competences and values in order to further the understanding of optimal development. The purpose of this research was to explore the relationship between the experience of Developmental Assets and adolescent’s perception of Life Satisfaction. A convenience sample of 503 Portuguese students was evaluated, mean age of 15.92 years (SD = 1.17), 63% female gender. Findings revealed that both external and internal Developmental Assets are experienced differently across gender, grade and age. Results indicate that 74% of the adolescents report their Life Satisfaction to be in the positive range. Boys report significantly higher levels of Life Satisfaction than girls. Results show significant negative correlations between Life Satisfaction and age. The main effect of school grade on Life Satisfaction was not statistically significant. Findings revealed that 32 of the 40 Developmental Assets configured in the model showed a statistically significant positive relationship with Life Satisfaction. Also, results suggest that the greater the experience of Developmental Assets, the greater the Life Satisfaction. Stepwise regression was conducted to determine which Developmental Assets and demographic factors predict Life Satisfaction. Results suggest that the relationship between demographic variables and Life Satisfaction is weak, contributing modestly to the prediction of Life Satisfaction (2%). Nine Developmental Assets emerged as independent and significant predictors of Life Satisfaction: Overall Self-esteem made the largest contribution, with Family Support, Planning and decision Making, Sense of Purpose, Positive Family Communication, Positive Values of Caring, Youth as Resources, School Engagement and Other Adult Relationships also yield significant predictability. The total regression model (Developmental Assets and demographic variables) explained 54% of the variance in Life Satisfaction results. The present findings suggest the applicability and utility of the framework as a strategy to foster positive development in adolescence.